LEGO DC comics super heroes character encyclopedia - Hugo, Simon; Scott, Cavan (New York, NY DK Publishing, 2016)
Presents the LEGO action figures based on the DC universe, describing each figure and vehicle, their variations, when they were made, and the playsets in which they appear
1
Keywords: Comic strip characters -- Juvenile literature; LEGO toys -- Juvenile literature; Models and modelmaking -- Juvenile literature; Superheroes -- Juvenile literature; Comic strip characters; LEGO toys; Models and modelmaking; Superheroes